Formal Verification of a Realistic Compiler. - Leroy, Xavier (Communications of the ACM, 2009)
This paper reports on the development and formal verification (proof of semantic preservation) of Comp Cert, a compiler from Clight (a large subset of the C programming language) to PowerPC assembly code, using the Coq proof assistant both for programming the compiler and for proving its correctness. Such a verified compiler is useful in the context of critical software and its formal verification: the verification of the compiler guarantees that the safety properties proved on the source code hold for the executable compiled code as well.